PELESTARIAN ASPEK BENTUK – FUNGSI ARSITEKTUR PURI SAREN AGUNG UBUD - BALI - Alwin Suryono (Prodi Arsitektur UNIVERSITAS KEBANGSAAN, 2023)
Abstract: Ubud, a dense tourism area originating from a rice field village, has Puri Saren Agung as a pioneer of Architectural Conservation. This paper aims to reveal the meaning of Bale Ukiran and Bale Gede (the main building of Puri Saren Agung), their significant architectural elements, and their conservation concept. Bale Ukiran a magnificent style of traditional Balinese architecture, limasan roof, red brick walls, multilevel open front terrace, its function is a place to receive guests, meetings and residence of the Puri family. The architectural/historical meaning is the splendor of the palace; Balinese cultural meaning of 'mountain - sea' and 'dualism of life' on terraced terraces; The meaning of the 'three layers of nature' in the carved ceiling - brick walls, wooden pillars - granite floor; The meaning of natural harmony on open terraces, wooden beams. Significant architectural elements: Limasan roof, terraced open terraces, carved ceiling-beams-doors-windows, brick walls. The building is maintained by adaptation, its function is preserved. Bale Gede is in the style of traditional Balinese architecture, with a thatch roof, open, its function is the place for Balinese religious/traditional ceremonies for the Puri family. The meaning of the architecture is sacred customary bale; The Balinese cultural meaning of the 'three layers of nature' through gold carvings on the underside of the roof - wooden pillars - granite floor; The meaning of the harmony of nature through the openness of buildings, wooden beams; The meaning of harmony between past and present life through the building remains as the original, the adaptation of the present in gold carvings, white granite floors. Significant architectural elements: Alang-alang roof, open, white floor at the highest level, gold carvings on the lower part of the roof. The building is maintained with few adaptations, its function survives.Abstrak: Ubud, kawasan pariwisata padat yang asalnya desa persawahan, memiliki Puri Saren Agung sebagai pionir Pelestarian Arsitektur. Tulisan ini bertujuan mengungkap makna Bale Ukiran dan Bale Gede (bangunan utama Puri Saren Agung), elemen arsitektur signifikannya, dan konsep pelestariannya. Bale Ukiran megah bergaya arsitektur Tradisional Bali, atap limasan, dinding bata merah, teras muka terbuka bertingkat, fungsinya tempat menerima tamu, pertemuan dan hunian keluarga Puri. Makna arsitektur/sejarahnya kemegahan istana; Makna Budaya Bali ‘gunung - laut’ dan ‘dualisme kehidupan’ pada teras bertingkat; Makna ‘tiga lapisan alam’ pada plafon berukiran - dinding bata, tiang kayu - lantai granit; Makna keharmonisan alam pada teras terbuka, tiang-balok kayu. Elemen arsitektur signifikan: Atap limasan, teras terbuka bertingkat, ukiran plafon-tiang-balok-pintu-jendela, dinding bata. Bangunan dipertahankan dengan adaptasi, fungsinya dipertahankan. Bale Gede bergaya arsitektur Tradisional Bali, atap persisai alang-alang, terbuka, fungsinya tempat upacara keagamaan/adat Bali keluarga Puri. Makna arsitekturnya bale adat sakral; Makna Budaya Bali ‘tiga lapisan alam’ melalui ukiran emas bagian bawah atap - tiang-tiang kayu - lantai granit; Makna keharmonisan alam melalui keterbukaan bangunan, tiang-balok kayu; Makna harmoni kehidupan masa lalu - masa kini melalui bangunan bertahan seperti aslinya, adaptasi masa kini pada ukiran emas, lantai granit putih. Elemen arsitetur signifikan: Atap tajug alang-alang, terbuka, lantai putih level tertinggi, ukiran emas bagian bawah atap. Bangunan dipertahankan dengan sedikit adaptasi, fungsinya bertahan.